ANALISIS PERKEMBANGAN PARIWISATA TERHADAP PERTUMBUHAN UMKM DI SUMATERA SELATAN - Yun Suprani; Zakiah . (JURNAL KOMPETITIF, 2019)
ABSTRACT The purpose of this study was to determine and analyze the development of tourism towards the growth of UMKM in South Sumatra. The type of data used is secondary data with documentation data collection techniques. The results of the study concluded that the tourism potential in South Sumatra is very large. There are many types of tours that can be offered to tourists, such as ecotourism, cultural tourism, and culinary. The development of the tourism sector can increase the growth of MSMEs because tourism involves many activities. Keywords: Tourism, UMKM